2021
DOI: 10.3390/encyclopedia1030052
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bioactive Extraction and Nano-Encapsulation

Abstract: An extraction technology works on the principle of two consecutive steps that involves mixture of solute with solvent and the movement of soluble compounds from the cell into the solvent and its consequent diffusion and extraction. The conventional extraction techniques are mostly based on the use of mild/high temperatures (50–90 °C) that can cause thermal degradation, are dependent on the mass transfer rate, being reflected on long extraction times, high costs, low extraction efficiency, with consequent low e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 183 publications
0
21
0
Order By: Relevance
“…Under constant stirring, 5 mL of saturated anhydrous sodium sulfate solution was added dropwise. A white precipitate settled down in the beaker and was separated out through filtration and completely dried at 60 °C [ 9 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under constant stirring, 5 mL of saturated anhydrous sodium sulfate solution was added dropwise. A white precipitate settled down in the beaker and was separated out through filtration and completely dried at 60 °C [ 9 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…This technique is particularly useful for application of bioactive materials in foods, cosmetics, and pharmaceuticals. The most common reasons for the use of nanoencapsulation are to protect components from loss of bioactivity from oxidation or thermal degradation, to reduce loss of volatiles, and for targeted drug delivery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…from fruits, nuts, and plant leaves, etc. [41]. In the present study, phenolic compounds were extracted from buckwheat hull employing both MAE and UAE strategies.…”
Section: Effects Of Novel Extraction Strategies On Recovery Yields Of...mentioning
confidence: 99%
“…The results showed the maximum extraction yield can be achieved at 4 • C due to the degradation of bioactive compounds at high temperatures. Likewise, some research [41] showed that the degradation of many phenolic compounds, including pigments, occurred at a high temperature (ca. 80 • C).…”
Section: Effects Of Novel Extraction Strategies On Recovery Yields Of...mentioning
confidence: 99%
“…Nevertheless, technological advances that promote large-scale production and generate high interest in the consumer market are demanded. Many of these strategies involve the action of ultrasound equipment, subcritical fluids, supercritical fluids, and enzyme-based extraction [27][28][29][30]. These technological advances promote higher concentrations than conventional methods such as Soxhlet extraction, maceration, and reflux methods, mainly due to the action of high pressures, temperatures and consequently, higher penetration of solvents into the plant matrix and prominent extraction of compounds [31].…”
Section: Introductionmentioning
confidence: 99%